The Potential Impacts of Religion and Spirituality on First Nation Teenage Fertility - Fonda, Marc (International Indigenous Policy Journal, 2013)
After reviewing some American research on the impacts religion has on adolescent sexual decision making and teenage pregnancy, this article considered the few instances of Canadian research addressing this topic. With this contextual information in place, it then moves on to report on analysis comparing the 2001 Census figures on religions declared by Canadian First Nation communities to teen fertility rates and the Community Well-Being Index (CWB). It finds that First Nations teen fertility rates are related to relative socio-economic deprivation, but also that religion has impacts on sexual decision making at the individual level and those First Nations communities showing no major religious adherence have teenage fertility rates of up to 140 per 1000, as compared to those communities showing one major tradition whose fertility rates are closer to 109 per 1000 adolescent First Nation women.